THE IMPACT OF CREATINE SUPPLEMENTATION ON COGNITIVE FUNCTION IN ELDERLY: A SYSTEMATIC REVIEW - Martyna Kaplińska; Dawid Siemieniuk; Aleksandra Kowalska; Hanna Wilska; Dominik Domoń; Dominika Domanowska; Adam Niedziela; Antoni Liebert; Natalia Klimek (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Age-related cognitive decline is a growing public health concern, affecting daily functioning and quality of life. Recent studies suggest that creatine supplementation may improve cognitive performance by supporting mitochondrial function and reducing oxidative stress. However, findings are mixed. This systematic review examines the effects of creatine supplementation on cognitive functions in older adults. Methods: A systematic review was conducted following PRISMA guidelines. PubMed/Medline and EMBASE databases (2003–2025) were searched using the phrase “the effect of creatine supplementation on cognitive functions in the elderly.” After screening 35 studies, four systematic reviews and meta-analyses met inclusion criteria. These studies assessed cognitive function through neuropsychological tests measuring memory, attention, executive function, and processing speed. Results: Meta-analyses indicated favorable effects of creatine on memory and processing speed in older adults. Xu et al. reported significant improvements in memory (SMD = 0.31, 95% CI: 0.18–0.44) and processing speed (SMD = −0.51, 95% CI: −1.01 to −0.01), with no significant effect on global cognition or executive function. Prokopidis et al. found the most pronounced effects in adults aged 66–76. McMorris et al. highlighted inconsistencies across studies, while Stares et al. found no additional benefit when creatine was combined with resistance training. Conclusions: Creatine supplementation may offer moderate cognitive benefits, particularly for memory and processing speed, in older adults—especially those with low baseline creatine or cardiovascular issues. Effects on global cognition and executive function appear limited. More high-quality, long-term randomized controlled trials are needed. Creatine’s neuroprotective properties may support its use in cognitive health strategies, especially alongside physical activity and proper nutrition.